1999
DOI: 10.1002/(sici)1521-3927(19991001)20:10<511::aid-marc511>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Ring-opening precipitation polymerization of poly(D,L-lactide-co-glycolide) in supercritical carbon dioxide

Abstract: SUMMARY: The biodegradable polymer poly(D,L-lactide-co-glycolide) was synthesized by a ring-opening precipitation polymerization in supercritical CO 2 using stannous octoate as initiator. Following polymerization, unreacted monomer was removed by supercritical fluid extraction and the polymer was recovered as a porous solid upon depressurization of the CO 2 phase. The lactide to glycolide ratio of the polymer was determined to be 70.7 : 29.3 using 13 C NMR spectroscopy. The weight-average molecular weight of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 14 publications
2
39
0
Order By: Relevance
“…Moreover, the availability of CO 2 as a byproduct of many industrial processes, its possible recycling, and easily accessible critical parameters account for its steadily increasing use. [164,165] The lipase-catalyzed transesterifications of a diester and diol were carried out in scCO 2 and supercritical fluoroform by Chaudhary et al and they reported that the molecular weight of the resulting polymer could be controlled by changing the pressure. [164] Hile and Pishko synthesized poly(lactide-co-glycolide) by a ring-opening precipitation polymerization in scCO 2 using stannous octoate as an initiator.…”
Section: Solvents For Green Polymer Production and Recyclingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the availability of CO 2 as a byproduct of many industrial processes, its possible recycling, and easily accessible critical parameters account for its steadily increasing use. [164,165] The lipase-catalyzed transesterifications of a diester and diol were carried out in scCO 2 and supercritical fluoroform by Chaudhary et al and they reported that the molecular weight of the resulting polymer could be controlled by changing the pressure. [164] Hile and Pishko synthesized poly(lactide-co-glycolide) by a ring-opening precipitation polymerization in scCO 2 using stannous octoate as an initiator.…”
Section: Solvents For Green Polymer Production and Recyclingmentioning
confidence: 99%
“…The weight-average molecular weight of the product was measured to be 3 400. [165] More recently, the ring-opening polymerization of CL initiated by dibutyltin dimethoxide was studied in scCO 2 at 40 8C at a pressure of 210-215 bar by Stassin et al [166] The molecular weight of the produced PCL was about 20 000.…”
Section: Solvents For Green Polymer Production and Recyclingmentioning
confidence: 99%
“…The emulsion and precipitation syntheses of poly(D,L-lactide-co-glycolide) using a CO 2 soluble SB, poly(perfluoroocytyl), were reported by Hile and Pishko. 29,30 Bratton et al 31,32 used blocks of PCL with KrytoxFSL and PCL-perfluoropolyether-PCL as SBs in PLLA synthesis in scCO 2 . A series of fluorinated diblock and triblock copolymers of PCL and poly(heptadecafluorodecylacrylate) were synthesized as SBs by the ring-opening polymerization of e-CL and atom transfer radical polymerization of the acrylate by Grignard et al 33 They used these copolymers in the dispersion ringopening polymerization of e-CL in scCO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…For medical applications, the presence of toxic substances from the production process in the final product is critical. For this reason, although polymerization can happen either in bulk or in solution media, the first one is desired for medical applications because of allowing to discard the presence of organic solvents traces in the polymer after reaction 4. Recently, there has been an interesting increase in the synthesis and the processing of these biomaterials using supercritical carbon dioxide (scCO 2 ) as reaction media 5.…”
Section: Introductionmentioning
confidence: 99%
“…This has allowed to study polymerizations of different monomers by a wide variety of mechanisms in supercritical solvents 6. However, few works have been devoted to the synthesis of PLGA in scCO 2 by ring‐opening polymerization (ROP),4, 5, 14 although homopolymerizations of lactide and other lactones, such as ε‐caprolactone, and their copolymerizations are described either in CO 2 or other supercritical fluids 15–22…”
Section: Introductionmentioning
confidence: 99%